Effects of Sn Incorporation in ZnO Thin Films on Properties of Perovskite Solar Cells - P. Malison (2020)
© Published under licence by IOP Publishing Ltd. Properties of electron transporting layer (ETL) play an important role on photovoltaic performances of perovskite solar cells. In this work, effects of Sn incorporation on properties of ZnO-based perovskite solar cells were investigated. Sn-doped ZnO (TZO) thin film as ETL was prepared via a sol-gel method. With 5% atom doping, TZO film coated on an indium doped tin oxide (ITO) substrate provided comparable light transmittance with that of an undoped ZnO/ITO substrate. It was also found that the optical band gap of TZO film (3.30 eV) is slightly wider than that of the ZnO one (3.28 eV). These results suggest that Sn atoms probably incorporated into the ZnO crystal during the sol-gel method. The grains size of perovskite layer coated on TZO or ZnO films also showed variation. The perovskite crystal on the TZO thin film (average 300 nm) was larger than that of the one on ZnO thin film (average 277 nm). The preliminary results indicate that the perovskite solar cell based on TZO film provided higher power conversion efficiency (PCE) of 4.42 % than the ZnO-based device (3.16%). Short-circuit current density (J sc), open-circuit voltage (V oc) and fill factor (FF) of TZO-based device were also higher than the ZnO-based device. This may be because TZO film may provide lower resistivity and better ETL/perovskite interface contact, confirmed by lower series resistance and higher shunt resistance of the TZO-based device. Finally, this work introduced a simple method to prepare TZO film at low temperature for photovoltaic application. It may help guide the development of flexible solar cells and other optoelectronic devices.